The Complete Book of Herbs - Clevely, Andi, 1945- and Richmond, Katherine (London Lorenz Books, 1994)
This book combines an A to Z of over 150 herbs, with practical advice on herb cultivation and a collection of recipes and craft ideas
Include Color Illustration and Index
Keywords: Cooking (Herbs) -- Herbs -- Herb gardening